Regional Development Planning Strategy Through the Digital Village Program to Realize the Welfare of Rural Communities - Himawan; Anik Vega Vitianingsih (Indonesian Journal of Applied and Industrial Sciences (ESA), 2023)
The Indonesian government's program through the construction of various infrastructure and facilities in various Indonesian regions has had positive impacts and benefits for the community. One of the development program plans launched by the government is to advance rural areas by using and utilizing information and communication technology (ICT) media. village area. The main focus that will be carried out in this research is to analyze the aspects that need to be improved by local governments in preparation for the transformation and implementation of digital villages. The research method that will be used in this research activity is to use descriptive analysis and combined with literature studies. The results of this research activity are in the form of a design for an internet network topology scheme and also a RAB which will be used as a cost estimate for the village government to prepare facilities and infrastructure for the construction of internet network infrastructure in village areas.